Eksistensi Gosip Di Media Sosial Dalam Menentukan Return Saham Di Bursa Efek Indonesia Dan Persistensi Pengaruhnya Bersama Hari Bursa - Sawidji Widoatmodjo; Halim Putera Siswanto (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
It is not easy to define whether a stock return is determined by a certain factor or trading days. There was much research evidence that some factors had influenced stock return. There were also, however, many types of research on stock return anomaly providing the facts that stock returns, especially their abnormal returns, were caused by specific trading days, such as week-day effect, January effect, and many others. This research attempts to explore this logic. We tested the impact of gossip that spread out through social media, as a certain factor, and all trading days in a week to a stock return. We used the gossip in social media as the response to the massive use of the internet in stock investment. The existence of the gossip is strengthened by the existence of noise traders. Nowadays, noise traders use the internet, such as mailing lists, message boards, Facebook, and others, which are called social media, as media to spread gossip. This research investigates whether gossips spread through mailing list have a role in mispricing, so then it can be used to determine the stock return. If they have the role, then how long is the persistence? To anticipate the impact of trading days, this research also includes trading days as a control variable. Using a multivariate statistical technique and combined with an event study with five windows (five days before and after a gossip has been posted), this research analyzes the stock return that gets the most gossip posted by investors. The result suggests that the gossip in social media do not show significant influence on the stock return, and automatically no persistence exists. Based on that result, the conclusion is that the gossip in social media can not be used to determine the stock return. The implication is that even social media can facilitate the stock transaction better, the investors in Indonesia Stock Exchange can not exploit the gossip in social media for taking profit through behaving as noise traders.